FREQUENCY AND RISK FACTORS OF SURGICAL SITE INFECTION IN ADULT MALES AGED 18-65 YEARS UNDERGONE INITIAL OPEN INGUINAL HERNIA REPAIR (Journal of Medical & Health Sciences Review, 2025)
BACKGROUND: Open inguinal hernia repair is most commonly performed procedure in general surgery and followed by surgical site infection in many cases. A wide range of infections are frequently observed and their predictive factors have been determined which lead to lot of variations and gaps in use of antibiotics prior to surgery. This study identifies factors which are predictive to development of surgical site infections in a group of male patients aged 18-65 years undergoing open inguinal hernia repair.OBJECTIVE: The objective of study was to find the frequency and risk factors of surgical site infection after open inguinal hernia repair in adult males aged 18-65 yearsMETHODS: This prospective study conducted on open and reducible inguinal hernia repair cases in adult males aged 18-65 years with clean surgical site and to whom prophylactic antibiotic was given according to SEAR guidelines 2018, selected through consecutive sampling from May to October 2024. Data collected was analyzed using SPSS version 25 to identify frequency and factors predictive of surgical site infection.RESULTS: This study conducted on 100 men aged 18-65 years showed a mean age of 56 years and an average operating time of 53 minutes. Variables like age, financial status, education level were found to be associated with surgical site infections and diabetes Mellitus, high BMI and current smoking have a statistically significant association with surgical site infections ( SSI) in adult males who  underwent open inguinal hernia repair.CONCLUSION: BMI >30Kg/ m2, Diabetes Mellitus and current smoking are high statistically significantly associated with Surgical site infection after initial ,open, reducible inguinal hernia repair in adult males with clean surgical site.